2013
DOI: 10.3390/ijms141121489
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Targeted Anti-Inflammatory Activity of Prunella vulgaris var. lilacina in Macrophages RAW 264.7

Abstract: Prunella vulgaris var. lilacina, a herbal medicine, has long been used in Korea for the treatment of sore throat, and to alleviate fever and accelerate wound healing. Although the therapeutic effect of P. vulgaris var. lilacina is likely associated with anti-inflammatory activity, the precise underlying mechanisms are largely unknown. Here, we sought to elucidate the possible mechanisms of the anti-inflammatory activity. We have investigated the anti-inflammatory activity of the various solvent fractions (hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…After 4 h of treatment, the cells were incubated with or without LPS (1 µg/mL) for 24 h. The culture mediums were collected and analyzed for IL-6, TNF-α, and PGE 2 production using ELISA kits according to the manufacturer's protocol. 21,22) To determine the total concentration of NO in the culture media, 150 µL of Griess reagent (1% sulfanilamide, 0.1% N-1-naphthylenediamine dihydrochloride and 2.5% phosphoric acid) was mixed with 150 µL of the supernatant and the absorbance at 540 nm was evaluated using a microplate reader. 23) Western Blot Analysis Preparations of whole cell lysates, cytoplasmic and nuclear fractions were carried out according to the previously published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…After 4 h of treatment, the cells were incubated with or without LPS (1 µg/mL) for 24 h. The culture mediums were collected and analyzed for IL-6, TNF-α, and PGE 2 production using ELISA kits according to the manufacturer's protocol. 21,22) To determine the total concentration of NO in the culture media, 150 µL of Griess reagent (1% sulfanilamide, 0.1% N-1-naphthylenediamine dihydrochloride and 2.5% phosphoric acid) was mixed with 150 µL of the supernatant and the absorbance at 540 nm was evaluated using a microplate reader. 23) Western Blot Analysis Preparations of whole cell lysates, cytoplasmic and nuclear fractions were carried out according to the previously published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we found that Prunella vulgaris var. lilacina possessed potent antioxidant and anti-inflammatory activities in vitro (19 , 20) . P. vulgaris var.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was performed in accordance with the manufacturer's instructions. 22) The concentration of PGE 2 was calculated with standard curve of PGE 2 .…”
Section: Measurement Of No and Pge 2 Concentrationsmentioning
confidence: 99%